(untitled) (Al-Academy, 2016)
The research current (Comment formal for Hruvijat in contemporary Iraqi porcelain). In an attempt to study the Arab character that inspired the Iraqi artist of all intellectual its terms of reference and stylistic by taking advantage of the cultural heritage and the rebuilding of the character to create a system ride of relationships that focus on structural body ceramic body ideas and multiple implications are invested in the structural fabric of the products of contemporary ceramic .vdila for ways to achieve and processing techniques and transmission of functional specificity (blogging) and cosmetic particularly to semantics derive from the content and expresses itself templates ceramic raw materials and by building works of art in plastic arts (ceramic) with two-dimensional and three-dimensional concepts that embody the implications raised directly or indirectly, which led to the detection of the correlation formal letter when Iraqi potters.Jaoualvsal the first ones to illustrate the problem of the research and its importance and the need for him .vdila goal represented by the following: - A correlation of formal character when Iraqi potters. As the second quarter came Mtkona of two sections, the first of it proved the concept of correlation and shape the technical concept and its applications, while the second section dealt with the diversity of calligraphy art and its uses, and an introduction to contemporary Iraqi porcelain. And Chapter III rules and regulations of search and selection of the sample is I mean I’ve covered the borders of Moldova Find the adoption of the descriptive analytical method. The fourth chapter included research and the results of which came from including, that the employment of the Arabic letter by some Iraqis contemporary potters, adopted on the basis of the character in full detail. And others used the style of distortion and simplification in the form of letters away from the rules of the system and expressed through all the semantic content and creative ways Mtaalqa with cultural heritage.He also sought contemporary Iraqi potter through the Arab employed for the character to serve and secured by the ceramic work in order to give the aesthetic value of the other.And then the conclusions that emerged from which the possibility of achieving the goals of research across the instrument taken by the researcher, also worked hard by mentioning a number of recommendations and proposals followed by a list of sources